2007
DOI: 10.1088/0953-8984/19/20/205139
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic poly-N-vinylpyrrolidone nanocarriers with incorporated model proteins

Abstract: New nanoscaled polymeric carriers have been prepared on the basis of different amphiphilic water-soluble derivatives of poly-N-vinylpyrrolidone (PVP). The polymer self-assembly and interaction with model proteins (Bowman-Birk soybean proteinase inhibitor (BBI) and its hydrophobized derivatives) were studied in aqueous media. The possibility of inclusion of both BBI and hydrophobized oleic acid derivatives of BBI in amphiphilic PVP aggregates was investigated. It was ascertained that polymeric particles of size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…This can be attributed to the strong hydrophobic interactions between the poorly soluble fluorescence probe and the nanoparticle core, resulting in compacting the particle structure to form smaller nanostructures. These results are in full agreement with data we previously obtained on the encapsulation of different hydrophobic drugs in Amph‐PVP nanoparticles . TEM and DLS studies also confirmed the spherical shape and narrow distribution of the pyrene‐loaded nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to the strong hydrophobic interactions between the poorly soluble fluorescence probe and the nanoparticle core, resulting in compacting the particle structure to form smaller nanostructures. These results are in full agreement with data we previously obtained on the encapsulation of different hydrophobic drugs in Amph‐PVP nanoparticles . TEM and DLS studies also confirmed the spherical shape and narrow distribution of the pyrene‐loaded nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The PVP amide group easily forms hydrogen bonds and as a result, PVP has a high binding affinity for several small and large molecules . In our previous studies, we have shown that PVP amphiphilic derivatives form spherical nano‐scaled micelle‐like assemblies (30–200 nm) at considerably low concentrations in aqueous media, which can effectively incorporate various low‐molecular and macromolecular drugs . The characteristics of these vesicles and drug loading efficiency (LE) can be easily controlled by polymer design and nanoparticle preparation conditions .…”
Section: Introductionmentioning
confidence: 99%
“…N-alkyl terminated (Amph-PVP) and di-n-alkyl terminated (Amph 2 -PVP) amphiphilic N-vinylpyrrolidone polymers were prepared using originally developed two-stage method as described in our previous studies (23,25). In the first stage, poly-Nvinylpyrrolidone (PVP) with one terminal carboxylic group was synthesized by free-radical polymerization of N-vinylpyrrolidone in the presence of initiator (azobisisobutyronitrile (AIBN) and chain-transmitter [mercaptoacetic acid (MAA)].…”
Section: Methodsmentioning
confidence: 99%
“…Since most drugs have a hydrophobic character, these drugs can be easily incorporated into the particle core by a covalent or a non-covalent bonding through hydrophobic interactions with the experimental methods such as direct dilution, dialysis (5), salting out procedure, or solvent evaporation method (24). In our previous study (25) we demonstrated the possibility of immobilization of model proteins (Bowman-Birk soybean proteinase inhibitor and its derivatives) on nano-scaled aggregates made of amphiphilic PVPs.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse delivery systems reported in the literature include liposomes, nanoparticles, microemulsions, and self-assembled polymeric nano and micro structures [6][7][8]. In this aspect, it has been previously shown that drug delivery systems based on amphiphilic poly-N-vinylpyrrolidone possess low toxicity, high biocompatibility, and stability, and can effectively entrap different low molecular weight and protein therapeutic agents [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%